Factors that influenced the eradication of corruption among Malaysian police / Noorhazura Ahmad Hamidi - Ahmad Hamidi, Noorhazura (Faculty of Business and Management, 2010)
The purpose of this research is to study the factors that influenced the eradication in corruption among Malaysian police. 100 employees in all 7 (seven) different departments; Criminal Investigation Division, Narcotics Criminal Investigation Division, Commercial Crime Investigation Department, Management Department, Logistic Department, Special Branch, and Public Order Department in Head Quarters Contingent Kuala Lumpur have been chosen as the respondents. The aspects that to be identified are income stagnation, government encouragement, and knowledge in personal financial management. The instrument of this study is questionnaire form. The sampling has been done probability sampling. The data was analyzed using SPSS Students version 14 for windows programs. Reliability statistic is used to measure the goodness of questionnaire being used. Descriptive statistic in terms of mean and frequency is used to analyze the awareness of financial planning and the corruption. The inference statistic that is t- test and multiple regression analysis is used to test the hypothesis. Results showed that the knowledge of personal financial management and income stagnation has no relationship in eradicate the corruption among police in Malaysia. While government campaign is most dominant factor which is have strong relationship with eradication of corruption.